Educational Protocol Proposal to promote the inclusion of students with hearing loss in mainstream classrooms - Olleta, Isabel; Sanz Manzanedo, Mónica; De la Natividad Sanz, Flavia (Auditio, 2025)
Thanks to universal newborn hearing screening programs, deafness is diagnosed early, enabling effective treatments with hearing aids and cochlear implants. This facilitates the development of functional oral language and promotes participation in educational and social activities, as long as effective and early access to interventions is guaranteed according to the type and degree of hearing loss. However, even with hearing devices, children may have difficulty understanding speech in noisy environments, which causes problems accessing academic content, attention difficulties, and auditory fatigue. In this study, based on a comprehensive literature review and an expert consensus process, it was concluded that ongoing training of teaching staff, families and students with and without hearing loss is key to promoting full inclusion in the school environment for students with hearing loss. As a result, a proposed school-based protocol is presented to train teachers, students and families about the educational, technological and psychosocial needs of children with hearing loss. In future studies, it is planned to evaluate the efficacy of the protocol through indicators of participation, academic performance and socio-emotional well-being.